2000
DOI: 10.1542/peds.105.4.822
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Assisted Ventilation: Predictors, Frequency, and Duration in a Mature Managed Care Organization

Abstract: Considerable variation exists in the utilization of ventilator support among infants of closely related gestational age. In addition, a number of medical risk factors influence the need for, and length of, assisted ventilation. These models explain much of the variance in LOV among preterm infants but explain substantially less among term infants.neonatal intensive care, assisted ventilation, Score for Neonatal Acute Physiology, resource consumption, prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 48 publications
2
33
3
5
Order By: Relevance
“…In order to compare the two systems, two similar prototypes were employed to conduct the gas flow required to the binasal prong (Hudson ® , n° 1) via the inspiratory limb of the circuit. The binasal has two anterior projections, each around 1 cm long, which were used separately; one of the passages allowed < 20% of the total gas flow to escape (bearing in mind that the nasal CPAP technique allows leakage around the baby s nostrils and/or mouth), while to the other nozzle a fixed resistance of 30 cmH 2 O/l/s was applied (to simulate the neonatal airway 20,22 ) and a test lung were connected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to compare the two systems, two similar prototypes were employed to conduct the gas flow required to the binasal prong (Hudson ® , n° 1) via the inspiratory limb of the circuit. The binasal has two anterior projections, each around 1 cm long, which were used separately; one of the passages allowed < 20% of the total gas flow to escape (bearing in mind that the nasal CPAP technique allows leakage around the baby s nostrils and/or mouth), while to the other nozzle a fixed resistance of 30 cmH 2 O/l/s was applied (to simulate the neonatal airway 20,22 ) and a test lung were connected.…”
Section: Methodsmentioning
confidence: 99%
“…22 This last has been considered to be a ventilation mode with advantages over conventional mechanical ventilation in certain clinical situations, proving efficient at CO 2 elimination and capable of reducing the duration of ventilatory support and oxygen therapy because it makes use of different gas transport mechanisms than does conventional mechanical ventilation. 21,22 Lee et al, studying newborn babies, observed vibrations similar to those found in our study. They state that the vibrations produced by the water seal CPAP s bubbling are transmitted to the chests of the babies on this type of ventilatory support and could contribute to gas exchange.…”
Section: Test Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…Low Apgar scores are associated with increased neonatal morbidity and mortality in preterm newborns, 6 increased mortality in VLBW infants, 7 increased neonatal mortality among preterm and term infants 5,7 and need for neonatal resuscitation. 8,9 STUDY DESIGN A retrospective two-time-period cohort design was used: births before the introduction of NRP, 1985NRP, -1988; and births after the introduction of NRP, 1991-1995, in Illinois. The transition training interval, 1989-1990, was excluded from analysis.…”
Section: Introductionmentioning
confidence: 99%